A generalization of Gelfand-Mazur theorem - Sung Guen Kim (International Journal of Mathematics and Mathematical Sciences)
In this paper, we show that if A is a unital semisimple complex Banach algebra with only the trivial idempotents and if σA(x) is countable for each x∈Fr(G(A)), then A≅C, this generalizes the Gelfand-Mazur theorem.